2006
DOI: 10.1364/ol.32.000096
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of spectral reflectance of object surfaces with the consideration of perceptual color space

Abstract: Due to the nonlinear transform from spectral reflectance to CIELAB values, the solution obtained by minimizing reflectance error in traditional spectral characterization methods will not be optimal when evaluated by colorimetric error. We propose a reflectance estimation method with consideration of perceptual color space. It combines two approaches, i.e., colorimetric-based spectral calculation and weighted spectral calculation. The experimental results show that the proposed method performs better than previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…It is impossible to recover r without any prior knowledge of the illumination and imaging system or any known targets [SX07]. Fortunately, many prior works have shown that spectral reflectance of most real‐world materials can be well represented by low dimensional data (usually 3 – 9) [PHJ89] (e.g.…”
Section: Problem Formulationmentioning
confidence: 99%
“…It is impossible to recover r without any prior knowledge of the illumination and imaging system or any known targets [SX07]. Fortunately, many prior works have shown that spectral reflectance of most real‐world materials can be well represented by low dimensional data (usually 3 – 9) [PHJ89] (e.g.…”
Section: Problem Formulationmentioning
confidence: 99%
“…A spectrophotometer is incapable of colour matching multicolour fabrics and samples of small sizes. With the development of digital imaging technology, multispectral imaging (MSI) systems have become available for extracting colour information of fabrics. An MSI system can provide not only the spectral information but also the spatial information of a sample compared with spectrophotometers.…”
Section: Introductionmentioning
confidence: 99%
“…This process is inefficient and error prone owing to inconsistency in preparing yarn samples [1]. With the development of digital imaging technology, multispectral imaging (MSI) systems [3][4][5][6][7] are adopted to extract the colour information of a fabric sample. MSI systems can provide not only the spectral information but also the spatial information of a sample.…”
Section: Introductionmentioning
confidence: 99%